Macrophage Activation and HIV Infection: Can the Trojan Horse Turn into a Fortress? - Herbein, G.; Coaquette, A.; Perez-Bercoff, D.; Pancino, G. (Current Molecular Medicine, 2002)
Macrophages are infected early during HIV infection and are thought to play the role of a Trojan horse by spreading infection in tissues. Most recent studies point out to a more complex role for macrophages in HIV infection: macrophages could contribute to both host defense and viral persistence and pathogenesis. Infected macrophages are a reservoir for HIV and modulate apoptosis of T cells present in their vicinity. Also, a functional impairment of HIV-infected macrophages may play a role in AIDS pathogenesis. Nevertheless, both activation and differentiation of monocyte / macrophages can interfere with susceptibility of these cells to infection. Therefore, a wide variety of stimuli result in HIV suppression through macrophage activation. At present times, a dynamic view on the role of macrophages in HIV infection arises which indicates that macrophages are a target for the virus and at the same time regulate its replication. Therefore, macrophages are at the cross-road between protection and pathogenesis in HIV infection due to their involvement both as a viral target and a key modulator of non-specific and specific immune responses. Future studies will help unravel the cellular and molecular mechanisms that underlie HIV-macrophage interactions and might result in new vaccine and / or therapeutic strategies.
Keywords: Macrophage Activation